Factors Influencing Suicidal Ideation in Persons with Physical Disabilities - Eun-Young Park (Behavioral Sciences)
Suicidal ideation is a leading indicator of suicide risk, particularly among persons with disabilities, a population at high risk of suicide. This study aimed to identify factors affecting suicidal ideation among persons with physical disabilities in Korea. Data for this cross-sectional study were obtained from the Disability and Life Dynamics Panel. Eight hundred and twenty-eight persons with physical disabilities were extracted from the data, and seven hundred seventy people who responded to the suicidal ideation question were included in the analysis. Chi-square and multivariate logistic regression analyses were employed. The results show a high percentage of suicidal ideation among persons with physical disabilities (18.5%). Among the general characteristics, more women were found to have suicidal ideation than men, and people in their 40s and 60s had a higher rate of suicidal ideation than other age groups. A lower educational level was found to be related to suicidal ideation. After controlling for general characteristics, depression increased the likelihood of suicidal ideation among individuals with physical disabilities. Economic difficulties and disability acceptance did not relate to suicidal ideation. Based on the results of this study, continuous observation of suicidal ideation in people with physical disabilities and early intervention programs for preventing depression and increasing disability acceptance are considered necessary.